The Application of Neuromarketing Techniques in the Spanish Advertising Industry: Weaknesses and Opportunities for Development - Baños-González, Miguel; Baraybar-Fernández, Antonio; Rajas-Fernández, Mario (Frontiers in Psychology, 2020)
Neuromarketing has aroused great interest in scientific research about consumer behaviour and, consequently, in the advertising industry, which is searching for an alternative to traditional techniques for measuring efficacy. However, despite its development in the academic world, in the professional sector, its use is still very limited. The aim of this work was to find out the perception of advertising professionals as regards neuromarketing techniques for identifying its advantages and disadvantages compared to other research techniques, as well as the reasons why the use of neuromarketing is so much lower than expected in the Spanish market. The technique chosen for data gathering was the semi-structured interview which made it possible to go into more depth with the subjects that came up. The interview, after a pre-selection of 100 professionals who matched the set criteria, was carried out individually, face-to-face, with a sample of 30 people with considerable professional experience in the field of marketing, sales communication and market research; all of them belonged to leading companies from the sector. Once the information had been categorized into units with common themes, the results obtained were interpreted to explain how neuromarketing techniques are being used in the field of advertising. The results obtained led us to the conclusion that, even though neuromarketing provides more objective data and it is closer to what really happens to consumers when they are exposed to an advertising message, the ignorance of its true possibilities, the inability of suppliers of these techniques to transmit the value they add to research, its complexity, its high cost and time requirements explain why it has had scarce use in advertising research. The results revealed the real reasons for the rejection of neuromarketing techniques which, in turn, will make it possible to introduce both technological and formative solutions, allowing it to be incorporated into future research designs.